دراسة بعض خواص الخرسانة الرغویة باعتماد سرعة الموجات فوق الصوتیة - nan, nan (Iraqi Journal of Civil Engineering, 2007)
Concrete is by far the most widely used construction material now today. Foamed concrete is light building material with good strength as well as low thermal conductivity and easy workability; it is produced by either Mix Foam Method or Preformed Foam Method. Ultrasonic Pulse Velocity(UPV) is a non destructive technique involve measuring the speed of sound through concrete in order to predict concrete strength and to detect the presence of cracking, voids, decay and other damages. This research includes three main experimental stages:- The first stage includes the production of foamed concrete and it was divided into two parts, the first part, mixing design(determination the proportions of the raw materials) was presented in the second part, the mixing procedure has been illustrated. The second stage includes preparation of samples,(i.e. molding, finishing surface, removal from molds, and curing). The third stage includes several teste to estimate properties the final product and factors influencing them, these properties include density, compressive strength, and the ultrasonic pulse velocity. From the experimental work and at the same test’s age, the compressive strength and the ultrasonic pulse velocity for foamed concrete with 800 kg/m3 density were respectively (2.38 MPa,1.56 km/s)and the compressive strength and the ultrasonic pulse velocity for foamed concrete with 1200 kg/m3 density were respectively (3.7 MPa,1.96 km/s) while it were (7.8 MPa and 2.12 km/s) for foamed concrete with 1600 kg/m3 density